KETIMPANGAN EKONOMI DALAM PERNIKAHAN : ANALISIS HUKUM ISLAM TERHADAP RELASI KUASA DAN QIWAMAH - Muhamad Ikram Shiddik Kusnadi; Teguh Dwi Cahyadi (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Women's financial independence in the modern era often triggers a masculinity identity crisis in men due to traditional gender ideology clashes. This study aims to analyze men's perceptions and anxieties regarding domestic economic inequality through contemporary Islamic Family Law. This qualitative thematic study utilized in-depth interviews with three Muslim men selected via purposive sampling until data saturation was reached. The findings reveal that men's anxieties stem from fears of losing domestic authority, reduced appreciation, and social pressure. However, Islamic law through independent property rights, proportional maintenance (nafkah), and a functional qiwāmah affirms that a husband's leadership is not automatically invalidated by income disparities. The novelty lies in shifting the gender studies focus from a female-centered view to male psychological burdens, demonstrating that men's concerns toward more established women are heavily influenced by patriarchal social constructions rather than normative Islamic principles. Implicitly, this study offers an equal partnership resolution for dual-earner couples and serves as a contextual guide for marriage counselors in applying nafkah and qiwāmah.